Income Analysis of Beef Cattle Farmers In Kadumbul Village, Pandawai District, East Sumba Regency - Iven Patu Sirappa; I Made Ade Sudarma; Sulkarnain Sulkarnain (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
Beef cattle farming is a side business and is still traditional in Kadumbul Village, Pandawai District, East Sumba Regency, where cattle farmers do not have records of expenditure and receipts. The purpose of this study is (1) to determine the characteristics of beef cattle farmers in Kadumbul Village, 2). To analyze beef cattle business income in Kadumbul Village, and 3). To find out the factors that affect beef cattle business income. Sample determination is determined by purposive sampling method. The data analysis used is qualitative analysis using revenue analysis. The results of research on the characteristics of beef cattle farmers in Kadumbul Village showed that the age range of 41-50 years was around 44%, junior high school category education was around 78%, livestock ownership of 1-2 ST was around 38%, and the average income of farmers from beef cattle business in Kadumbul Village for a year was Rp.21, 290,938/year/farmer, with an average livestock ownership of 5 ST. Factors that affect farmers' income are livestock ownership and production costs, while the variables of experience, family responsibility, and age do not affect beef cattle business income.